Some Remarks on the Development of Labor Law in the Protectorate of Bohemia and Moravia - Jaromír Tauchen (Journal on European History of Law, 2010)
This document examines the transformation of labor law in the Protectorate of Bohemia and Moravia, highlighting the substantial state interventions in employment relationships and the imposition of labor control systems, including forced labor. It discusses the integration of National Socialist ideology into labor law, aiming to align work with the interests of the Volksgemeinschaft (national community), and the impact on individual rights, particularly affecting the Jewish population.